Impacts of climate change on basin vegetation based on Biome-BGC model: A case study with the Jialing River Basin - Chuansen Wu; Xiaoning Hou; Shanghong Zhang; Weiyi Zhou; Yang Zhou (PLoS ONE, 2026)
Vegetation, as a key component of land cover, plays a vital role in regulating energy exchange and water balance at different spatial and temporal scales. It is thus important to explore dynamic processes of changes in vegetation cover under changing environmental conditions in the context of global climate change. In this study, the Jialing River Basin (JRB) was selected as a case study, with the leaf area index (LAI) used as the primary indicator to represent JRB vegetation cover and growth status. The Biome-BGC model was employed to simulate the growth of various vegetation types within the basin. We calibrated the optimal range of multiple physiological and ecological parameters of vegetation and analyzed vegetation responses to climate change. The results showed that under four CMIP6 climate scenarios (SSP126, SSP245, SSP370, and SSP585), both temperature and precipitation in the basin are projected to increase. From 1976 to 2016, the vegetation coverage of the basin remained high, and on a monthly timescale, the grasslands are more responsive to climate-induced variability than woodlands. Under the influence of a warmer, more humid climate from 2023 to 2100, the LAI of vegetation in the basin is projected to show an increasing trend, and the vegetation coverage of woodland will still exceed that of grassland. These findings contribute to a more accurate simulation of vegetation dynamics under climate change and can inform the development of effective vegetation conservation and management strategies.